PENGARUH JENIS DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) - A.A.A.S. Trisnadewi; T.G.O. Susila; I.W. Wijana (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
The experiment that aimed to study the types and various levels of manure for improving growth and production of sweet corn was conducted for 9 weeks. Completely randomized design (CRD) arranged with nested model was used in this experiment. The main plot consisted of three kind of manures, there were broiler manure (A), horse manure (K), and pig manure (B). As sub plot were levels of manure: without manure D0 (0 ton/ha), D1 (10 ton/ha = 87.51 g/pot), D2 (20 ton/ha = 175 g/pot), D3 (30 ton/ha = 262.5 g/pot), with three replication in each combination treatment. Variables measured in this experiment were plant high, stem diameter, fresh and dry weight of leaf, stem and maize-ear of corn, total dry weight of forage production (stem + leaf) and dry weight ratio of stem and leaf of sweet corn. The result of the experiment showed that the effect of broiler, horse, and pig manure on all variables which measured in the experiment were not significantly different (P>0,05). The highest growth and production of sweet corn were obtained at 20 ton/ha level for all kind of manures that used in this experiment with total dry weight of forage production 48.88; 51.11; and 48.30 g/pot and dry weight of maize-ear production 23.80; 23.30 and 22.00 g/pot for broiler, horse and pig manure respectively. Based on results of the experiment it can be concluded that no different effect on type of manure (broiler, horse and pig) to the growth and production of sweet corn and the using manure at 20 ton/ha level give the highest growth and production of sweet corn.